PENGARUH PENGETAHUAN DAN PERILAKU PENAMBANG NIKEL TERHADAP PENGELOLAAN LINGKUNGAN HIDUP PADA PT. KONAWE NIKEL NUSANTARA KECAMATAN LANGGIKIMA KABUPATEN KONAWE UTARA - Arsyad, Laode Muhammad; Hajar, Ibnu; Adam, La Ode Bahana (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to determine and analyze the influence of the knowledge and behavior of nickel miners on environmental management at PT. Konawe Nikel Nusantara in Langgikima Subdistrict, North Konawe Regency. The sample in this study consists of some employees of PT. Konawe Nikel Nusantara in Langgikima Subdistrict, North Konawe Regency, totaling 60 people. This research uses multiple linear regression analysis. The results of the study indicate that: (1) Knowledge and behavior of nickel miners have a positive and significant effect on environmental management at PT. Konawe Nikel Nusantara in Langgikima Subdistrict, North Konawe Regency. (2) Knowledge has a positive and significant effect on environmental management at PT. Konawe Nikel Nusantara in Langgikima Subdistrict, North Konawe Regency. (3) The behavior of nickel miners has a positive and significant effect on environmental management at PT. Konawe Nikel Nusantara in Langgikima Subdistrict, North Konawe Regency.